PELATIHAN PENGELOLAAN KEUANGAN SECARA DIGITAL MELALUI APLIKASI AKUNTANSI PADA UKM TAMAN KOTA BATAM - Wisnu Yuwono; Johny Budiman; Riskiyanto Riskiyanto; Santo Santo; Piere Ricardo; Jesni Jesni; Sindy Sindy; Agustini Fatmasari; Lydia Lestari; Yessica Stephanie Lim (National Conference for Community Service Project (NaCosPro), 2020)
The purpose of this community service program is to assist SME in Taman Kota Batam in managing digital finance with application. The use of accounting application makes it very easy for SMES to generate financial reports automatically. In the implementation of this community service program, we made a direct visit to our partners in the Taman Kota and asked about their bookkeeping system, conducted an analysis of the data obtained, conducted an application test, and provide training to partners for the operation of SME accounting application in one semester. The result of implementation showed that SMEs problems can be solved digitally in financial records, saving quite a lot of time, and making it easier to classify money for every expenditure and income transactions.